2013
DOI: 10.5511/plantbiotechnology.13.0304a
|View full text |Cite
|
Sign up to set email alerts
|

ATL54, a RING-H2 domain protein selected by a gene co-expression network analysis, is associated with secondary cell wall formation in Arabidopsis

Abstract: Biosynthesis of plant secondary cell walls is controlled by several master transcription factors. Ubiquitin ligases, which mediate ubiquitination of proteins, including transcription factors in the protein degradation pathway, are also believed to regulate secondary wall biosynthesis; however, the exact ubiquitin ligases involved in secondary wall formation have not yet been identified. We conducted a gene co-expression network analysis and found that ATL54, annotated as a RING-finger protein, was highly co-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Our previous study suggested that ATL54 may be involved in the regulation of programmed cell death as well as secondary wall formation during xylogenesis (Noda et al 2013). In this study, the tissue-level expression pattern analysis demonstrated that ATL54 was expressed in stem interfascicular fibers, xylary fibers, and vessels ( Figure 1A-D).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Our previous study suggested that ATL54 may be involved in the regulation of programmed cell death as well as secondary wall formation during xylogenesis (Noda et al 2013). In this study, the tissue-level expression pattern analysis demonstrated that ATL54 was expressed in stem interfascicular fibers, xylary fibers, and vessels ( Figure 1A-D).…”
Section: Discussionmentioning
confidence: 72%
“…MYB46 is known to be a positive regulator of secondary wall biosynthesis (Ko et al 2009;Zhong et al 2007), while it was shown that overexpression of MYB46 did not activate XCP1 and XCP2, the genes related to programmed cell death during xylogenesis (Zhong et al 2007). In our previous study, we showed that the expression of secondary wall biosynthetic genes in apical stem portions was up-regulated by knock-out of ATL54 (Noda et al 2013), suggesting that ATL54 may act as a negative regulator of secondary wall biosynthesis. Spatially and temporally accurate lignin deposition and vessel element differentiation are known to be controlled by the action of both negative and positive regulators Zhao et al 2008;Zhao and Dixon 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations